Development of a knowledge-based piping diagnostic system using a knowledge organization approach - Ni, ChunQing. (2008)
Knowledge sorting is one way to organize the knowledge acquired from the domain expert(s) and various sources. Well-organized knowledge representation will make rule extraction much easier. In this work, a knowledge sorting process was adapted to facilitiate the rule extraction for a knowledge-based diagnosing piping system.